2014
DOI: 10.1007/s00345-014-1357-7
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: En bloc transurethral resection with 2-micron continuous-wave laser for primary non-muscle-invasive bladder cancer: a randomized controlled trial

Abstract: The authors' affiliation was incorrect in the original publication. It did not include the vital Grant information as well. The correct affiliation details and the funding information are mentioned here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…By reading the full text of 38 cations, 17 studies were eventually included [14-16, 21-34], comprising 2,439 participants. Of the 17 studies, 6 were RCT [23-25, 27, 29, 32] and the rest were retrospective cohort studies [14-16, 21, 22, 26, 28, 30, 31, 33, 34]. The included studies ranged from 2010 to 2018, with a median follow-up of 24 months (range: 12–64 months).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…By reading the full text of 38 cations, 17 studies were eventually included [14-16, 21-34], comprising 2,439 participants. Of the 17 studies, 6 were RCT [23-25, 27, 29, 32] and the rest were retrospective cohort studies [14-16, 21, 22, 26, 28, 30, 31, 33, 34]. The included studies ranged from 2010 to 2018, with a median follow-up of 24 months (range: 12–64 months).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 14 studies [14-16, 21-26, 29-32, 34], involving 1,847 patients, showed that the incidence of obturator nerve reflex during transurethral laser surgery was significantly lower than with TURBT through a fixed-effects model meta-analysis (OR = 0.04; 95% CI 0.02–0.09; p < 0.00001). I 2 = 0% meant that no significant heterogeneity was found (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…En bloc resection, which consists of removing an entire tumor in one piece, aims to enhance diagnostic accuracy and provide an oncologic benefit through complete resection without spillage of tumor cells [ 48 ]. Originally described using monopolar electrocautery [ 49 ], it has also been performed using laser resection [ 50–52 ], and with a water-jet-aided hydrodissection technique for larger tumors [ 53 ]. Oncologic outcomes are currently under investigation in a randomized trial [ 54 ].…”
Section: Diagnosis and Stagingmentioning
confidence: 99%